Patologi Birokrasi dalam Penyelenggaraan Pelayanan Publik Tingkat Kecamatan di Takalar - Ammas, Sitti; Hasran, Hasran; Hasran, Bachtiar; Fitriani, A. (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Sinjai, 2023)
This study aims to identify and analyze the forms of bureaucratic pathology and public service at the sub-district office in Takalar Regency and to identify and analyze efforts to overcome the pathology of bureaucracy and public services at the sub-district level of Takalar Regency. In this study using a qualitative descriptive research type, while collecting data using observation techniques, in-depth interviews, and literature study. The research results show that in general the performance of the bureaucracy in carrying out public services at the sub-district level in Takalar Regency is considered not optimal. There is even an information gap in the form of the public not knowing the procedures and procedures for service, as well as the responsiveness of the apparatus to various complaints experienced by service users.